Olive oil ameliorates allergic response in murine ovalbumin-induced food allergy by promoting intestinal mucosal immunity - Yu Ma; Ming Liu; Donghui Li; Jie Li; Zixin Guo; Yunjun Liu; Shengnan Wan; Yixiang Liu (Food Science and Human Wellness)
The numerous health benefits of olive oil are widely known, however, it also provides anti-allergic properties that have not yet been fully defined. In this study, the anti-allergic activity of olive oil was evaluated by analyzing the clinical symptoms and immune-related factors in BALB/c mice that had ingested 600 mg/(kg∙day) olive oil for two weeks prior to the evaluation. An allergy model was subsequently constructed for analysis, the results of which showed that the olive oil reduced the scores of allergic symptoms in the mice, and up-regulated the hypothermia and the decline in the immune organ index. Moreover, fewer allergy-related cytokines and reduced intestinal inflammation was discovered in the olive oil-treated group. In addition, analysis of intestinal mucosal immune-related factors revealed that the olive oil promoted the expression of intestinal tight junction proteins (Claudin-1, Occludin, and ZO-1) and IL-22, and helped maintain the integrity of the intestinal epithelial physical barrier. Increased levels of mucin 2 and β-defensin were also found in the intestinal mucus of the olive oil-treated mice. These findings suggest that the oral administration of olive oil effectively attenuated the ovalbumin-induced allergic immune response in the mice, and had a positive effect on intestinal epithelial mucosal immunity.